Parent Perspectives of Behavioral and Emotional Development of Young High-Ability Children: A Pilot Study - Benna S. Haas; Laura S. McCorkle; Thomas W. Connors; Erin R. FitzPatrick; Michael S. Matthews; Julianna Willis (Education Sciences)
We conducted a thematic analysis of 25 parent responses to open-ended survey questions from the Behavioral Assessment System for Children (BASC-3) regarding their young, high-ability children’s behavioral and emotional development. Our analysis revealed four themes: (a) demonstrating advanced abilities, (b) displaying motivation to do well, (c) enjoying the company of adults and peers, and (d) experiencing difficulties regulating emotions. Further, three themes from parents of young typically developing children were also included as a comparison: (a) demonstrating academic strengths, (b) connecting with others, and (c) experiencing difficulties regulating emotions. These themes provide a first step in informing classroom teachers, counselors, and psychologists about young children’s social, emotional, and behavioral needs and matching them with appropriate educational programming and intervention options. This paper also includes implications of the findings and suggestions for further research to maximize young children’s gifts, talents, and exceptionalities.